Characteristics, Management and Survival Rate of Ovarian Germ Cell Tumor: Karakteristik, Manajmen dan Tingkat Kesintasan Ovarian Germ Cell Tumor - Laila Nuranna; Zakiah Tourik (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Objective:To determine the prevalence of malignant ovarian germ cell tumour in term of characteristics, management, and 3-year survival rate in Dr. Cipto Mangunkusumo Hospital Jakarta from 2011 to 2013. Methods: This is a cross-sectional study. Secondary data were collected from medical record as well as interviewing patients through phone call or home visit. Results: We collected data from 24 subjects. As many as 54.2% of subjects were between 20 to 40 year old, and 58.3% was single. Around 83.3% of the subjects came with chief complaint of abdominal enlargement. Histopathology finding confirmed dysgerminoma in 50% subjects, mixed ovarian germ cell tumour in 25%, endodermal sinus tumour or yolk sac tumour in 16.7%, and immature teratoma in 8.3%. Half of the cases were found in stage I. The primary therapy was conservative surgical staging and adjuvant chemotherapy.In 2 subjects with dysgerminoma, neoadjuvant chemotherapy (bleomycin, etoposide, cisplatin, and cyclophosphamide-cisplatin regimen) resulted in a good response. The 3-year survival rate was 83.3% in dysgerminoma, 100% in mixed ovarian germ cell tumour, and 50% in immature teratoma. Conclusion: In malignant ovarian germ cell tumour, conservative surgical staging followed by a complete course of chemotherapy is the treatment of choice with 3-year survival rate exceeding 70%. Keywords: dysgerminoma, non-epithelial ovarian tumour,ovarian germ cell tumour, survival Abstrak Tujuan : Mengetahui sebaran meliputi karateristik, penatalaksanaan dan kesintasan 3 tahun pasien tumor ganas sel germinal ovarium di RSCM tahun 2011 – 2013. Metode : Penelitian ini menggunakan studi potong lintang dengan mengambil data sekunder dari rekam medis dan mewawancarai pasien atau keluarga pasien via telepon atau kunjugan rumah. Hasil : Pada penelitian ini, dari 24 subjek penelitian, 54,2% ditemukan pada usia 20-40 tahun dan 58,3% subjek belum menikah. Sebanyak 83,3% datang dengan keluhan perut membesar. Secara histopatologi didapatkan jenis disgeminoma, tumor sel germinal campuran, sinus endodermal (yolk sac) dan teratoma imatur dengan proporsi masing-masing 50%, 25%, 16,7% dan 8,3%, sebagian besar kasus (50%) ditemukan pada stadium I. Conservative surgical staging dan kemoterapi adjuvan tatalaksana pilihan. Terdapat 2 subjek jenis disgerminoma yang diberikan dengan kemoterapi neoadjuvan (regimenbleomycin, etoposide, cisplatin dan cyclophosmide-cisplatin) memberikan respon yang baik. Kesintasan ≥ 3 tahun pada jenis disgerminoma mencapai 83,3%, pada tumor sel germinal campuran 100% dan pada teratoma imatur mencapai 50%. Kesimpulan : Pada tumor ganas sel germinal ovarium conservative surgical staging diikuti kemoterapi lengkap merupakan pilihan terapi dengan kesintasan ≥ 3 tahun mencapai > 70%. Kata kunci : disgerminoma,kesintasan, tumor ovarium non epithelial, tumor sel germinal ovarium.